2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2012
DOI: 10.1109/icassp.2012.6288723
|View full text |Cite
|
Sign up to set email alerts
|

Existence and estimation of impropriety in real rhythmic signals

Abstract: Impropriety in complex signal processing has been studied and used primarily in a communications context, but also in some cases where complex signals are generated by adding real signals in quadrature. We discuss the meaning of impropriety, and the associated use of complementary statistics, when a real-valued random process is improper in the frequency domain. Through the use of modulation signal models, spectral impropriety can be connected explicitly to the frequency and phase of components belonging to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Clark et al examined the spectral impropriety of real-valued signals in [10]. Here we do the same, though with a different formulation.…”
Section: Connection To Spectral Improprietymentioning
confidence: 89%
“…Clark et al examined the spectral impropriety of real-valued signals in [10]. Here we do the same, though with a different formulation.…”
Section: Connection To Spectral Improprietymentioning
confidence: 89%
“…Recently, several researchers have begun analyzing the noncircularity of real-valued signals in complex-valued transform domains. In particular, Clark, Kirsteins, and Atlas [16] studied the spectral circularity of real time-domain signals using a modulation model and showed that certain properties of a real timedomain signal can produce noncircularity in the spectral domain. In the work presented here, we study the circularity of complex-valued subbands for a class of signals modeled on voiced speech.…”
Section: A Backgroundmentioning
confidence: 99%
“…As in (1), we demodulate the signal with a complex exponential of frequency and apply a lowpass filter. When , the subband is given by (14) Assuming that the cutoff frequency of is lower than , the subband is (15) The sample circularity coefficient for is (16) Substituting the relation in (15), (16) reduces to (17) Thus, ; the perfectly demodulated sinusoid is rectilinear.…”
Section: Signal Subband Noncircularitymentioning
confidence: 99%
See 1 more Smart Citation
“…This work highlights the importance of SOS characterization for complex analysis of Gaussian RVs and higher order statistics for other RVs. Many real-world problems render improper random signals in diverse fields requiring appropriate analysis and treatment e.g., in medicine [6], [20], [21], [102], [124], [145]- [147], oceanography [13], [148], [149], geology [12], [14]- [16], [103], [150]- [152], optics [10], [153], [154], acoustics [11], [155], [156], power systems [18], [19], [157], [158]. and communication systems [4]- [7], [9], [22]- [26], [28], [32], [48], [67]- [69], [107], [108], [159]- [161].…”
Section: Overviewmentioning
confidence: 99%